2020
DOI: 10.1111/are.14626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fishmeal replacement with cottonseed protein concentrate on growth, digestive proteinase, intestinal morphology and microflora in pearl gentian grouper (♀ Epinephelus fuscoguttatus  × ♂ Epinephelus lanceolatu )

Abstract: A 56-day feeding trial was conducted to study the effects of cottonseed protein concentrate (CPC) as fishmeal (FM) replacement on growth, digestive proteinase, intestinal morphology and microflora in pearl gentian grouper (♀Epinephelus fuscoguttatus × ♂Epinephelus lanceolatu). FM of 0% (FM), 12.00% (R12), 24.00% (R24), 36.00% (R36), 48.00% (R48) and 60.00% (R60) was replaced with CPC, to prepare six diets and feed groupers. Weight gain (WG) and specific growth rate (SGR) were highest in the R24 group, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 67 publications
4
44
0
Order By: Relevance
“…Several studies have recently addressed the suitability of different raw materials for TGGG hybrid grouper, including soybean protein concentrate (SPC) 35,89,90 cottonseed protein concentrate, 89,91 haemoglobin meal 92 mixed rendered animal proteins 93 and poultry meal. 94 Those that have addressed raw materials have looked at the TA B L E 5 Summary of vitamin requirement studies for grouper species capacity of specific raw materials to replace fish meal protein, and the results are therefore a combination of our knowledge on the value of fish meal and the value of the alternative proteins being tested.…”
Section: Su Itab Le R Aw Materials Smentioning
confidence: 99%
“…Several studies have recently addressed the suitability of different raw materials for TGGG hybrid grouper, including soybean protein concentrate (SPC) 35,89,90 cottonseed protein concentrate, 89,91 haemoglobin meal 92 mixed rendered animal proteins 93 and poultry meal. 94 Those that have addressed raw materials have looked at the TA B L E 5 Summary of vitamin requirement studies for grouper species capacity of specific raw materials to replace fish meal protein, and the results are therefore a combination of our knowledge on the value of fish meal and the value of the alternative proteins being tested.…”
Section: Su Itab Le R Aw Materials Smentioning
confidence: 99%
“…According to the methods of Chen et al (2020), microbiome sequencing technology was used to detect the hybrid grouper intestinal microbiota, with the assistance of Biomarker Technologies Co., Ltd. (Beijing, China). The microbiome analyses of the samples of each treatment were performed in triplicate.…”
Section: Intestinal Microbiome Analysismentioning
confidence: 99%
“…As a new type of plant protein, cottonseed protein concentrate (CPC) has recently received much attention from researchers (Wan et al, 2018;Ye et al, 2020). Accordingly, the experimental replacement of fish meal with CPC has been conducted for certain aquaculture species, such as hybrid grouper (Chen et al, 2020), juvenile golden pompano (Trachinotus ovatus) (Shen et al, 2020), and pacific white shrimp (Litopenaeus vannamei) (Wan et al, 2018). However, researchers have found that replacing fish meal with high levels of CPC can decrease growth performance and cause intestinal inflammation issues in hybrid groupers (Yin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With 60 g/kg EH addition, the Shannon index was significantly and diversity of intestinal bacterial communities were significantly increased compared with other groups. The dominant bacterial phyla in vertebrates include Proteobacteria, Firmicutes and Bacteroidetes (Chen et al., 2020; Qin et al., 2010; Ye et al., 2020), which accounted for 86.30%, 87.93%, 64.02%, 84.88% and 86.32% of the relative abundances of the entire flora in groups EH0, EH3, EH6, EH9 and EH12, respectively. The top 10 dominant phyla and genera had no significant difference in category.…”
Section: Discussionmentioning
confidence: 99%
“…Since vegetable protein sources are rich in protein and relatively cheap, many researchers have studied their use as potential FM substitutes for feeding to hybrid groupers. These include cottonseed protein concentrate (Chen et al., 2020; Yin et al., 2018), soy protein concentrate (Faudzi et al., 2018) and low‐gossypol cottonseed protein (Ye et al., 2020). Such research has reduced the FM content and cost of fish feed (Ye et al., 2019; Zhang, Pu, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%